Spies and Holy Wars The Middle East in 20th-Century Crime Fiction - Simon, Reeva Spector (University of Texas Press, 2021)
Illuminating a powerful intersection between popular culture and global politics, Spies and Holy Wars draws on a sampling of more than eight hundred British and American thrillers that are propelled by the theme of jihad-an Islamic holy war or crusade against the West. Published over the past century, the books in this expansive study encompass spy novels and crime fiction, illustrating new connections between these genres and Western imperialism. Demonstrating the social implications of the popularity of such books, Reeva Spector Simon covers how the Middle Eastern villain evolved from being the malleable victim before World War II to the international, techno-savvy figure in today's crime novels. She explores the impact of James Bond, pulp fiction, and comic books and also analyzes the ways in which world events shaped the genre, particularly in recent years. Worldwide terrorism and economic domination prevail as the most common sources of narrative tension in these works, while military "tech novels" restored the prestige of the American hero in the wake of post-Vietnam skepticism. Moving beyond stereotypes, Simon examines the relationships between publishing trends, political trends, and popular culture at large-giving voice to the previously unexamined truths that emerge from these provocative page-turners